A new biomimetic route to engineer enzymatically active mechano-responsive materials. Issue 26 (26th February 2015) - Rios, César; Longo, Johan; Zahouani, Sarah; Garnier, Tony; Vogt, Cédric; Reisch, Andreas; Senger, Bernard; Boulmedais, Fouzia; Hemmerlé, Joseph; Benmlih, Karim; Frisch, Benoît; Schaaf, Pierre; et al.
Abstract : Uniaxial stretching of β-galactosidase anchored to a cross-linked polyelectrolyte multilayer leads to the tuning of the material catalytic activity. Abstract : Using modified β-galactosidase covalently linked to cross-linked polyelectrolyte multilayers (PEM), catalytically active materials have been designed. Their enzymatic activity can be modulated, partially in a reversible way, simply by stretching. This strategy, based on enzyme conformational changes, constitutes a new tool for the development of biocatalytic mechano-responsive materials.